Caribbean Report 28-02-1997 - Gordon, Warren (anchor); Richards, Ken (correspondent); Ninvalle, Pete (correspondent); Anthony, Kenny (interviewee); Lansico, Romanas (interviewee); Fraser, Tony (correspondent); Panday, Basdeo (interviewee); Fray, Bobby (interviewee); Grant, Jennifer (correspondent) (The British Broadcasting Corporation, 1997)
In research undertaken by the American Association for World Health, the inclusion of food and medicine in the US embargo against Cuba is being challenged. Next, in Jamaica a PNP political activist is gunned down in Kingston. Next, both political parties have raised the possibility of violence in St. Lucia’s upcoming general elections which are constitutional due in April. In the following segment, another member of parliament has defected from the opposition to the government. He has declared himself an independent and without a few hours accepts a ministerial post from the Prime Minister of Trinidad and Tobago. In the final segment, one of Britain’s most famous actresses has died of a heart attack.
1. Headlines (00:00:32)
2. The inclusion of food and medicine in the US embargo against Cuba is being challenged. Ken Richards reports (00:33-02:34)
3. Former PNP member gunned dowm in Jamaica. Jennifer Grant reports from Kingston, Jamaica (02:35-04:41)
4. The prospect of violence in St. Lucia's forthcoming general election is examined. Prime Minister of St Lucia, Kenny Anthony and Romanas Lansico, PRO of the ruling United Workers Party and Tourism and National Mobilisation Minister are interviewed (04:42-07:31)
Keywords: US embargo -- Cuba.; American Association for World Health.; Davy, Clinton.; Jingles.; General elections -- St Lucia.; Violence -- St Lucia.; United Workers Party -- St Lucia.; Griffith, Rupert.; People's National Movement -- Trinidad and Tobago.; Defection -- Member of Parliament.; Srinath, Javagal.; Samuels, Robert.; Lucas, Isabel.